Changes in biochemical and microbiological parameters of Mola (Amblypharyngodon mola) fish pickle during storage at room temperature - Hossain, Md Ismail; Shikh, Fatema Hoque; Shohan, Sanjida (Fundamental and Applied Agriculture, 2019)
Among small indigenous species (SIS) of fishes Mola (Amblypharyngodon mola) has high nutritive value. Beside traditional curry preparation it is necessary to make available this highly nutritive fish in other ‘ready to eat’ forms and also adding value to this fish. Therefore, this study was carried out to prepare fish pickle with Mola (Amblypharyngodon mola) and to observe the changes in biochemical parameters and bacterial load of this pickle stored at room temperature (28°C to 32°C). The study was conducted in the Department of Fisheries Technology Laboratory, Bangladesh Agricultural University. The results of the study showed that the percent moisture and protein content decreased while lipid and ash content increased after preparation of pickle than those of fresh fishes. The fish pickle stored at room temperature (28°C to 32°C) in sealed and vacuum sealed packing conditions, the percent moisture, protein and lipid content decreased with the progress in storage period gradually but ash content increased. At this temperature (at both sealed and vacuum sealed pack), pH value of the pickle decreased very slowly but the TVB-N value and bacterial load increased gradually throughout the storage period. So, it was concluded that, at room temperature (28°C to 32°C) shelf life of Mola (Amblypharyngodon mola) fish pickle was short, pickle may remain in acceptable condition until 12 days in sealed pack and 30 days in vacuum sealed pack.